Soil management systems and sand hydric behaviour on coconut palms growth - Fontes, Humberto R.; Costa, Liovando M. da (Pesquisa Agropecuaria Brasileira, 2014)
The effect of soil management systems and sand hydric behaviour on coconut palms growth and on chemical and physical properties of coastal sand were studied. The effect of disk harrowing system (G), mechanical mowing (R) and manual cultivation (A) on some physical and chemical characteristics of the soil were evaluated comparing the results to the original results obtained under natural vegetation. Plant growth was evaluated in the second and third years, by number of leaves, number of leaflets on leaf number 3, and girth circumference. Analysis of leaf number 4 was accomplished on three-year-old plants' samples. Uncovered soil by disk harrowing in dry season increased nitrogen level in leaf 4, and plant growth. The largest proportion of a very thin sand (0,10 - 0,05 mm) was responsable for microporosity increase and consequent water capacity increase, mainly at low pressures.